Analysis Of The Influence Of Social Media Influencers, Herding Bias, Information Quality On Student Invesment Decisions UPN ‘Veteran’ East Java Mediated By Fear Of Missing Out (FOMO) - Winda Amalia Sari; Takarini, Nurjanti (UNIVERSITAS PAKUAN, 2025)
This study examines the effects of social media influencers, herding bias, and information quality on the investment decisions of 119 UPN Veteran East Java students, with FOMO as a mediator. Using PLS-SEM analysis via SmartPLS, results show that herding bias (β = 0,002, p < 0.05) and information quality (β = 0,001, p < 0.05) directly influence investment decisions, while social media influencers affect decisions indirectly through FOMO (β = 0,331, p < 0.05). FOMO significantly mediates the relationship between these factors and investment behavior, highlighting the key role of social and psychological influences in students’ digital investment choices.